Self-healing ability based on hydrogen bonds in organic coatings for corrosion protection of AA1200 - Nardeli, Jéssica V. [UNESP]; Fugivara, Cecílio S. [UNESP]; Taryba, Maryna; Montemor, M. F.; Benedetti, Assis V. [UNESP] (Elsevier, 2020)
Biobased polyurethane coatings derived from vegetable oils, with 2 different compositions, were prepared and applied on the AA1200 aluminum alloy to confer corrosion protection. The influence of the ratio between the polyester (flexible segment) and the prepolymer (rigid segment) was investigated. Infrared spectroscopy studies evidenced the difference between the areas of the bands (–NH) and optical and scanning electron microscopy evidenced the morphological features of the coating surface before and after immersion in aggressive medium. The barrier properties and anti-corrosion performance of the coatings were evaluated by electrochemical impedance spectroscopy and the results revealed an increase of impedance over the immersion time. Localized corrosion studies confirmed the self-healing effect in coatings formulated with the highest content of polyester.
Keywords: Aluminum alloy; Biobased coatings; Corrosion protection; LEIS; Self-healing; SVET/pH micro-potentiometry